The capacity of exosomes derived from adipose-derived stem cells to enhance wound healing in diabetes - Cai, Feiyu; Chen, Wenjiao; Zhao, Ruomei; Liu, Yi (Frontiers in Pharmacology, 2023)
The slow healing and nonhealing of diabetic wounds have long posed challenges for clinical practitioners. In the presence of elevated glucose levels, the body's regulatory mechanisms undergo alterations that impede normal wound healing processes, including cell proliferation, cytokine release, and growth factor activity. Consequently, the advancement of stem cell technology has sparked growing interest in utilizing stem cells and their derivatives as potential therapeutic agents to enhance diabetic wound healing. This paper aims to provide an academic review of the therapeutic effects of adipose-derived stem cell-EXOs (ADSC-EXOs) in diabetic wound healing. As a cell-free therapy, exosomes (EXOs) possess a multitude of proteins and growth factors that have been shown to be advantageous in promoting wound healing and mitigating the potential risks associated with stem cell therapy. By examining the current knowledge on ADSC-EXOs, this review seeks to offer insights and guidance for the potential application of EXOs in the treatment of diabetic wounds.